CRITIQUE OF STABILITY LIMITS OF THE UHPM INDEX MINERALS DIAMOND AND COESITE - Liu L.-G. (My University, 2002)
The transition boundaries for the graphite ↔ diamond and quartz ↔ coesite reactions are reviewed. The recommended linear transition boundaries are P (kbar) = 15 + 0.028 T (°C) for the graphite ↔ diamond transition, and P (kbar) = 22 + 0.009 T (°C) for the quartz ↔ coesite transition. The recommendation was made on the basis of reliable transition boundaries determined at high-pressure and high-temperature experiments and their consistency with the thermochemical calculation of the transition pressures at room temperature. The recommended boundary for the graphite ↔ diamond transition is about 2 kbar higher, and that for the quartz ↔ coesite transition is about 1.5 to 3.5 kbar higher than those adopted in the literature to constrain the P-T conditions of UHPM origin.